The Children's City : a building renewal movement for the Philippine Children's Medical Center - Quizon, John Lyndon C. (Manila : National University, 2017)
The new medical approach to reducing hospital patient care, especially post-surgical care has been a major influence in the planning of recent hospitals. More spaces are being allocated to departments that handle specialized diagnostic and therapeutic techniques.
Chapter 1. The Problem and it's settings -- Chapter 2. Research Methodology -- Chapter 3. Terms and Reference -- Chapter 4. Data Gathering, Collection and Analysis of Data -- Chapter 5. Design Framework -- Chapter 6. Translations -- Bibliography -- Appendices.
Includes bibliographical references.
Keywords: CHILDREN'S HOSPITAL -- PHILIPPINES